A family care model for older persons with hip-fracture and cognitive impairment: A randomized controlled trial. (August 2021) - Tseng, Ming-Yueh; Yang, Ching-Tzu; Liang, Jersey; Huang, Huei-Ling; Kuo, Li-Min; Wu, Chi-Chuan; Cheng, Huey-Shinn; Chen, Ching-Yen; Hsu, Yung-Heng; Lee, Po-Cheng; Shyu, Yea-Ing L.
Abstract: Background: Dementia and hip fracture are both associated with substantial disability and mortality. However, few studies have explored the effects of intervention programs on post-operative recovery of older persons with hip fracture and cognitive impairment. Objective: To examine the effects of a family-centered care model for older persons with hip fracture and cognitive impairment and their family caregivers. Design: Single-blinded clinical trial. Setting: A 3000-bed medical center in Taiwan. Participants: Older persons hip fracture and cognitive impairment ( N  = 152); 76 in the intervention group, and 76 in the usual-care control group. Methods: A family-centered care model consisting of geriatric assessment, discharge planning, in-home rehabilitation, and family caregiver-training for dementia care. Outcomes were assessed 1-, 3-, 6- and 12-months following hospital discharge for older persons with hip fracture and cognitive impairment. Assessed outcomes were self-care ability (performance of activities of daily living and instrumental activities of daily living), nutritional status, self-rated health, health-related quality of life and self-efficacy, and competence of the family caregivers. Results: Relative to patients who received usual care, those who received the family-centered care intervention had a greater rate of improvement in self-rated health (β = 1.68, p < .05) and nutritional status (β = 0.23, p < .05), especially during the first 6 months following hospital discharge. Relative to family caregivers who received usual care, those who received family-centered care had a higher level of competence (β = 7.97, p < .01), a greater rate of improvement in competence (β = 0.57, p < .01), and a greater rate of improvement in self-efficacy (β = 0.74, p < .05) 3 months following hospital discharge. Conclusions: A family-centered care model enhanced family caregivers' self-efficacy and competence but did not improve the physical recovery of the participants with hip fracture and dementia. We suggest adding an educational component to include geriatric assessment, discharge planning, in-home rehabilitation, and family caregiver-training for dementia care and assessing family caregiver outcomes in interventions for older persons with hip fracture and cognitive impairment. Trial registration: Registered with www.clinicaltrials.gov (NCT03894709) Tweetable abstract: A family-centered care model consisting of geriatric assessment, discharge planning, in-home rehabilitation, and family caregiver-training for dementia care of older persons with hip fracture and cognitive impairment enhanced family caregivers' self-efficacy and competence.